PENERAPAN METODE LEAST SQUARE UNTUK PREDIKSI PENJUALAN BRIGHT GAS 5,5 KG - Serwin; Lasena, Yulianti (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
This company sells 5.5 kg of Bright gas which will be distributed to the base every month, experiencing ups and downs. In addition, it also resulted in the inappropriate procurement of 5.5 kg Bright gas. Every month it is not adjusted to monthly sales estimates because it has not used a prediction system. Therefore, there is a sales prediction system of 5.5 kg of bright gas every month, the amount of bright gas is 5.5 kg which will be distributed to the base. The purpose of this research is to find out good accuracy in the Least Square method for the selling process of 5.5 kg bright gas at PT. Togo Jaya Gorontalo. Results achieved With the bright gas prediction system, predictions can be made for the next period and measurement results using MAPE of 0.20%.